Formulation, optimization and characterization of apremilast-loaded nanosponges for potential topical wound management applications - Purnima Rai; Ajay Kumar Singh Rawat (Creative Pharma Assent, 2026)
Background: Topical drug delivery systems provide site-specific therapy with reduced systemic exposure. Nanosponges have emerged as promising carriers owing to their porous structure, enabling improved drug stability, bioavailability, and sustained release. Apremilast, a phosphodiesterase-4 (PDE4) inhibitor with anti-inflammatory activity, has potential for topical wound management when formulated as a controlled-release delivery system. Methods: Apremilast-loaded nanosponges were prepared by the emulsion solvent diffusion method using Ethyl Cellulose (EC) and Polyvinyl Alcohol (PVA). A 3² factorial design was used to optimize the EC: PVA ratio and sonication time. Formulations were evaluated for particle size, entrapment efficiency, zeta potential, in vitro drug release, and surface morphology. Characterization included UV spectroscopy, FTIR, XRD, DSC, and SEM. Drug release kinetics were analyzed using mathematical models. Results: Preformulation studies confirmed drug purity and compatibility with excipients. The optimized formulation (NS8) exhibited a particle size of 213.85 nm, an entrapment efficiency of 82.75%, a zeta potential of −33.3 mV, and a sustained drug release of 95.85% over 24 h. SEM revealed spherical porous nanosponges, while FTIR, XRD, and DSC confirmed drug integrity and formulation stability. Response surface analysis demonstrated significant effects of formulation variables on performance. Drug release followed the Higuchi model (R² = 0.987), and the Korsmeyer–Peppas exponent (n = 0.58) indicated anomalous non-Fickian diffusion. Conclusion: Apremilast-loaded nanosponges demonstrated sustained drug release, excellent stability, and favorable physicochemical characteristics, indicating their potential as an effective topical delivery system for wound management. Further ex vivo, in vivo, and clinical studies are required to confirm therapeutic efficacy and safety.